Effects of voice disguise on speaking fundamental frequency - Künzel, Hermann J. (International Journal of Speech, Language and the Law, 2000)
Patterns of voice disguise in forensic cases involving speaker identification or speaker profiling may contain clues to features of the undisguised voice of a speaker. In a longitudinal and synchronous study, 100 subjects were asked to read a text on five occasions during a period of six months, first using their normal voices, and subsequently with two out of three modes of voice disguise, (1) raising fundamental frequency, (2) lowering fundamental frequency, (3) denasalization by firmly pinching theirnose. The focus of this investigation is on fundamental frequency (F0). Results show that most subjects were in fact able consistently to change their F0 according to the mode of disguise they had selected. However, there were differences between both sexes with regard to their preference of disguise modes as well as to the individual articulatory ‘strategies’ which they employed to implement them. Results corroborate experience with forensic casework, that is, they show that there is a constant relation between the F0 of a speaker’s natural speech behaviour and the kind of disguise he willuse in an incriminating phone call. Speakers with higher-than-average F0 tend to increase their F0 levels. This process may or may not involve register changes from modal voice to falsetto. Speakers with lower-than-average F0 prefer to disguise their voices by lowering F0 even more and often end up with permanently creaky voice. Thelatter trend can be observed much more clearly in males. Females are generally more reluctant to make drastic changes to their fundamental frequency patterns.